Organização do museu de paleontologia e estratigrafia Paulo Milton Barbosa Landim - Bertini, Reinaldo José [UNESP]; Bertini, Lília Maria Dietrich [UNESP]; Jacconi, Laís Lima [UNESP]; Silva, Claudio Ribeiro da [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This project sought to reorganize the Museum of Paleontology and Stratigraphy "Paulo Milton Barbosa Landim," in search for a better service to visitors. It is important in refining the reception to the public, in the Extension Project to the community that the Museum develops. This organization comprises renew cabinets storefronts, including disposal of the samples; review and update the content of existing texts, retracing the labels, placing them in acrylic holders. The ultimate goals are to make the most complete and attractive display for visitors. Additionally make casts of fossils and separate spare materials for donation.

Este Projeto pretende reorganizar o Museu de Paleontologia e Estratigrafia “Paulo Milton Barbosa Landim”, na busca de um melhor atendimento para os visitantes. Importante no refinamento para a recepção ao público, no âmbito do Projeto de Extensão à comunidade que o Museu desenvolve. Esta organização compreende renovar as amostras e disposição nos armários expositivos; rever e atualizar o conteúdo dos textos existentes, refazendo as etiquetas, colocando-as em suportes de acrílico, tornando a exposição mais completa e atraente para os visitantes. Adicionalmente confeccionar réplicas de fósseis e separar materiais sobressalentes para doação.
Keywords: Museum; Fossils; Sedimentary rocks; Organization; Museu; Fósseis; Rochas sedimentares; Organização